Prevalence and characteristics of metabolic syndrome in South-East Asian psoriatic patients: A case-control study - Chayada Kokpol (2018)
© 2014 Japanese Dermatological Association. The prevalence of metabolic syndrome in Asian psoriatic patients compared with that of the general population shows variable results. This study aimed to examine the association between psoriasis and metabolic syndrome in a Thai population. This case-control study included 199 psoriatic patients and 199 controls matched for sex and age from the general Thai population. There were 111 men (55.8%) and 88 women (44.2%) in both the psoriatic and control groups. The mean age (± standard deviation) of both groups was 50.04 ± 13.81 and 49.96 ± 14.39 years (P = 0.91), respectively. The majority of psoriatic cases (82.9%) were of plaque type. The prevalence of metabolic syndrome was significantly higher in psoriatic patients than in the general population at 49.25% versus 30.65%. After controlling for age, sex, smoking and alcohol drinking the odds ratio was 2.25 (P < 0.0001). The metabolic components which were significantly higher in the cases than controls included hyperglycemia, high blood pressure (HBP) and abdominal obesity. No statistically significant difference was found between the cases and controls regarding prevalence of obesity, hypertriglyceridemia and low high-density lipoprotein cholesterol. Thai psoriatic patients had a higher prevalence of metabolic syndrome than the general population. In conclusion, the prevalence of HBP, hyperglycemia and abdominal obesity was significantly higher in cases than in controls.